Dracula or Frankenstein? The role of the international community in the 2014 Afghan presidential elections. Issue 6 (1st November 2016) - Smith, Scott S.
Abstract: The 2014 presidential elections in Afghanistan were a major test of internationally led democratisation efforts in that country since 2001. They took place at a time of uncertainty, when the international community was withdrawing from Afghanistan, and in the shadow of the fraud-ridden 2009 elections that had required international intervention to resolve. The author situates the international attempt to ensure successful 2014 elections within the wider global paradigm shift over the past decade from elections as a means of self-determination to elections as a means of generating and ensuring international security. The focus on security meant that when the 2014 election did generate a political crisis in Afghanistan that threatened to destabilise the country, the international community intervened heavily in a way that undermined the future prospects of democratisation in Afghanistan. As well as questioning this intervention, the author describes a general pattern of international involvement in Afghanistan that tended to undermine sovereignty, overlook the importance of generating consensus among Afghan political actors, and badly misjudge timelines required to implement logistical processes.